2001
DOI: 10.1177/107155760100800309
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Inhibition of Presynaptic Catecholamine Synthesis With α-Methyl-Para-Tyrosine Attenuates the Circadian Rhythm of Human TSH Secretion

Abstract: Through its inhibitory effect on TRH, norepinephrine appeared to be involved in the regulation of TSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, previous clinical studies ( Engelman et al 1968 a , b , Nasrallah et al 1977 , Nicoletti et al 1986 , Perry et al 1990 , Sand et al 1997 , Steinsapir et al 1997 , Zimmermann et al 2001 , Wachtel et al 2015 , Butz et al 2017 , Hamidi et al 2017 , Naruse et al 2018 , Takekoshi et al 2019 ) did not assess the effects of αMPT on glucose metabolism (Supplementary Table 1, see section on supplementary materials given at the end of this article). Additionally, whether αMPT administration enables safe surgical treatment remains unclear, even though αMPT is indicated to effectively reduce MN and normetanephrine (NMN) levels.…”
Section: Introductionmentioning
confidence: 96%
“…However, previous clinical studies ( Engelman et al 1968 a , b , Nasrallah et al 1977 , Nicoletti et al 1986 , Perry et al 1990 , Sand et al 1997 , Steinsapir et al 1997 , Zimmermann et al 2001 , Wachtel et al 2015 , Butz et al 2017 , Hamidi et al 2017 , Naruse et al 2018 , Takekoshi et al 2019 ) did not assess the effects of αMPT on glucose metabolism (Supplementary Table 1, see section on supplementary materials given at the end of this article). Additionally, whether αMPT administration enables safe surgical treatment remains unclear, even though αMPT is indicated to effectively reduce MN and normetanephrine (NMN) levels.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have demonstrated that administration of AMT increases endogenous prolactin levels both in animals and humans [6][7][8][9]. Thus, measuring AMT concentrations in plasma could help establish AMT pharmacokinetics and also aid in potentially developing a pharmacoki- netic/pharmacodynamic (PK/PD) model between AMT and prolactin.…”
Section: Introductionmentioning
confidence: 99%